ANALISIS KEMAMPUAN MEMECAHKAN MASALAH DAN KOMUNIKASI MATEMATIS SISWA SD DI KABUPATEN MANGGARAI NTT - Marselina Lorensia (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2017)
This research aims to describe the ability in problem solving and the communication skills of the Manggarai Elementary school students; furthermore, investigate the particular aspects needed to pay attention more. This is a descriptive research which was conducted in elementary schools in Manggarai District in April 2014. The subjects of this research are 39 students from 13 elementary schools in Manggarai. The instruments which are utilized are test items, assessment sheets, the ability in problem solving, mathematical communication and interview guideline. The result of the research presents 39 students who become the subjects of the research, did not give the perfect answers towards the test items. Concerning the problem solving ability, the research result shows that not all aspects of problem solving are performed by the students. Concerning the mathematical communication, the research results show that the students’ ability in stating the mathematical situation into mathematical points of idea has been performed well; nevertheless, the elaboration of the problem solving stages are still poor. Based on the research results, it can be summed up that the ability of problem solving and mathematical communication of the students in Manggarai District elementary schools are poor.